2014
DOI: 10.1002/cncr.28961
|View full text |Cite
|
Sign up to set email alerts
|

Agent Orange exposure and cancer incidence in Korean Vietnam veterans: A prospective cohort study

Abstract: BACKGROUND During the Vietnam War, US and allied military sprayed approximately 77 million liters of tactical herbicides including Agent Orange, contaminated with 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin. To the authors' knowledge, few studies to date have examined the association between Agent Orange exposure and cancer incidence among Korean veterans who were exposed to Agent Orange during the Vietnam War. METHODS An Agent Orange exposure index, based on the proximity of the veteran's military unit to the area th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 35 publications
0
73
0
Order By: Relevance
“…The most recent group in which associations have been estimated between Agent Orange exposure and risk of NHL, HL, and MM is the cohort of South Korean veterans of the Vietnam War [126,127]. Studies in this group include a cross-sectional analysis of self-reported cancer prevalence based on a postal survey completed by 114,562 veterans [126] and a retrospective cohort study of cancer incidence among 180,251 veterans linked to the national cancer incidence database [127].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most recent group in which associations have been estimated between Agent Orange exposure and risk of NHL, HL, and MM is the cohort of South Korean veterans of the Vietnam War [126,127]. Studies in this group include a cross-sectional analysis of self-reported cancer prevalence based on a postal survey completed by 114,562 veterans [126] and a retrospective cohort study of cancer incidence among 180,251 veterans linked to the national cancer incidence database [127].…”
Section: Methodsmentioning
confidence: 99%
“…Studies in this group include a cross-sectional analysis of self-reported cancer prevalence based on a postal survey completed by 114,562 veterans [126] and a retrospective cohort study of cancer incidence among 180,251 veterans linked to the national cancer incidence database [127]. Potential exposure to Agent Orange was evaluated based on the proximity of the respondent's division or brigade (and, in the cross-sectional study, based on the proximity of the respondent's self-reported battalion or company) to sprayed areas, using the Agent Orange Exposure Opportunity Index model E4 developed by Stellman et al [128].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations